MODEL PEMBELAJARAN KOOPERATIF DALAM MENUMBUHKAN KEAKTIFAN BELAJAR SISWA - Zuriatun Hasanah; Ahmad Shofiyul Himami (Irsyaduna: Jurnal Studi Kemahasiswaaan, 2021)
Cooperative learning provides opportunities for students to study with fellow students in structured assignments. Through cooperative learning as well, a student will become a learning resource for his other friends. So cooperative learning is developed on the basis of the assumption that the learning process will be more meaningful if students can teach each other. Although in cooperative learning students can learn from two main learning sources, namely teaching and other study partners. cooperative learning can make students interact between students to share their knowledge in solving a problem presented by the teacher so that all students will more easily understand various concepts, create an atmosphere of acceptance towards fellow students with different backgrounds, for example ethnic, social, cultural, and ability. This provides equal opportunities to all learners regardless of background and creates conditions for cooperation and positive interdependence with each other in completing tasks. Teaches collaboration or collaboration skills in solving problems. These skills are very important for students as a provision for living in society. In addition, students learn to respect each other.